(untitled) (Minerva, 2019)
The Hellenistic period and Late Antiquity witnessed a notable development of the literary form of commentaries on classical texts. The present article analyzes the rhetorical, juridical, and philosophical origins of the main principles of this hermeneutics, then describes its systematization and use in commentaries by Neoplatonic authors on the works of Plato and Aristotle, as well as by Christian authors on the Bible. By way of hypothesis, it is proposed that the hermeneutical principles involved may be classified according to the three basic elements of communication (author, message and reader), in the following manner: the author’s intention, the text’s meaning (literal and allegorical), and the reader’s utility.